Mathematical model for intermittent microwave convective drying of food materials. Issue 8 (10th June 2016) - Kumar, C.; Joardder, M. U. H.; Farrell, T. W.; Millar, G. J.; Karim, M. A.
ABSTRACT: Intermittent microwave convective drying (IMCD) is an advanced technology that improves both energy efficiency and food quality in drying. Modeling of IMCD is essential to understand the physics of this advanced drying process and to optimize the microwave power level and intermittency during drying. However, there is still a lack of modeling studies dedicated to IMCD. In this study, a mathematical model for IMCD was developed and validated with experimental data. The model showed that the interior temperature of the material was higher than the surface in IMCD, and that the temperatures fluctuated and redistributed due to the intermittency of the microwave power. This redistribution of temperature could significantly contribute to the improvement of product quality during IMCD. Limitations when using Lambert's law for microwave heat generation were identified and discussed.